If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 + -1x = 7 + -1x Reorder the terms: -2 + 3x + -1x = 7 + -1x Combine like terms: 3x + -1x = 2x -2 + 2x = 7 + -1x Solving -2 + 2x = 7 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -2 + 2x + x = 7 + -1x + x Combine like terms: 2x + x = 3x -2 + 3x = 7 + -1x + x Combine like terms: -1x + x = 0 -2 + 3x = 7 + 0 -2 + 3x = 7 Add '2' to each side of the equation. -2 + 2 + 3x = 7 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 7 + 2 3x = 7 + 2 Combine like terms: 7 + 2 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| -17+21=-4(x+4) | | 32=(2*9)+2w | | 9-9x-7-12x=5 | | 5ln(x+9)-4lnx= | | 1.8x+9=5.7x-6 | | 3T-2=5T+6 | | 2=0.14285714285(4)+c | | 5x-2x+x=15 | | 3x^2-5x-1=2 | | 4a*2+12ab+96*2= | | y^2-3y+10=0 | | 16-7x=-4-3x | | -9-9x=-18-18x | | 49x=20x+2030 | | 2+6x=72 | | 187=l*11 | | -4(t-4+8t)=6t-8 | | x^3-4x^2-49x=-196 | | (5rq^3)(-3r^4q)=0 | | x-2=-5X-1 | | 5c^3+15c^2-270c=0 | | -x^2+12x=-3 | | 2n-3=3n+2 | | 3x+1-4x+8=3x-4x+6 | | 6x+4=-24+x | | -4x-8=-16-8x | | 7+2x=-5x-14 | | 5x-9=10x-59 | | 3x/2-7=x/4-2 | | 9x+9=-x+39 | | 50.2+.02= | | 7x^2+22x+3=3 |